The Interaction between Antioxidants Content and Allergenic Potency of Different Raspberry Cultivars - Ewelina Hallmann; Alicja Ponder; Mateusz Aninowski; Tuya Narangerel; Joanna Leszczyńska (MDPI AG, 2020)
Food allergies are a very serious problem among consumers. The most common food allergies involve animal products, but they can also involve fruits such as berries. We aimed to determine whether organic farming is useful for the production of high-quality and safe fruits. Three varieties of raspberries 'Laszka', 'Glen Ample' and 'Polka' from organic and conventional production (neighboring farms) were collected over the two years of the experiment. Quantitative and qualitative analysis of phenolic compounds was carried out, and the content of Bet v1 and profilin was determined. The organic raspberries contained a lower level of phenolic compounds, especially anthocyanins. Conventional fruits were characterized by a higher allergenic potency than organic ones. We found a strong link between their anthocyanin content and the allergy status of conventional raspberry fruits. Therefore, organically produced raspberries are safer for consumers.